TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization: a specialized Tau perspective - Kapoor, Mahima; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2023)
Microtubule-associated protein, Tau has been implicated in Alzheimer's disease for its detachment from microtubules and formation of insoluble intracellular aggregates within the neurons. Recent findings have suggested the expulsion of Tau seeds in the extracellular domain and their prion-like propagation between neurons. Transforming Growth Factor-beta 1 (TGF-beta 1) is a ubiquitously occurring cytokine reported to carry out immunomodulation and neuroprotection in the brain. TGF-beta-mediated regulation occurs at the level of neuronal survival and differentiation, glial activation (astrocyte and microglia), amyloid production-distribution-clearance and neurofibrillary tangle formation, all of which contributes to Alzheimer's pathophysiology. Its role in the reorganization of cytoskeletal architecture and remodelling of extracellular matrix to facilitate cellular migration has been well-documented. Microglia are the resident immune sentinels of the brain responsible for surveying the local microenvironment, migrating towards the beacon of pertinent damage and phagocytosing the cellular debris or patho-protein deposits at the site of insult. Channelizing microglia to target extracellular Tau could be a good strategy to combat the prion-like transmission and seeding problem in Alzheimer's disease. The current review focuses on reaffirming the role of TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization and considers utilizing the approach of TGF-beta-triggered microglia-mediated targeting of extracellular patho-protein, Tau, as a possible potential strategy to combat Alzheimer's disease.
Keywords: Alzheimer's disease; Cytoskeleton reorganization; Extracellular Tau; microglia; TGF-beta; TGF-beta 1